2001
DOI: 10.1007/s004420100758
|View full text |Cite
|
Sign up to set email alerts
|

Influence of climate-driven shifts in biomass allocation on water transport and storage in ponderosa pine

Abstract: Conifers decrease the amount of biomass apportioned to leaves relative to sapwood in response to increasing atmospheric evaporative demand. We determined how these climate-driven shifts in allocation affect the aboveground water relations of ponderosa pine growing in contrasting arid (desert) and humid (montane) climates. To support higher transpiration rates, a low leaf:sapwood area ratio (A L /A S ) in desert versus montane trees could increase leaf-specific hydraulic conductance (K L ). Alternatively, a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
100
4
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(122 citation statements)
references
References 57 publications
7
100
4
3
Order By: Relevance
“…The large majority of studies in mature stands reported a positive relationship between precipitation or soil water availability and LAI, when moisture transects included a turnover of tree species or forest communities (for example, Grier and Running 1977;Kozlowski and Pallardy 1997;Bussotti and others 2000;Eamus 2003;Prior and others 2005). In studies with only one tree species, a reduction in LAI with decreasing rainfall was found in certain temperate coniferous stands (Gower and others 1992;Mencuccini and Grace 1994;Hebert and Jack 1998;Maherali and DeLucia 2001) and in species-poor tropical forests in Hawaii (Harrington and others 1995;Austin and Vitousek 1998;Ares and Fownes 1999). However, we are only aware of one study (Bussotti and others 2000) along a rainfall gradient focusing on the LAI of a temperate broad-leaved tree species.…”
Section: The Leaf Area-water Supply Relationship In Forestsmentioning
confidence: 95%
“…The large majority of studies in mature stands reported a positive relationship between precipitation or soil water availability and LAI, when moisture transects included a turnover of tree species or forest communities (for example, Grier and Running 1977;Kozlowski and Pallardy 1997;Bussotti and others 2000;Eamus 2003;Prior and others 2005). In studies with only one tree species, a reduction in LAI with decreasing rainfall was found in certain temperate coniferous stands (Gower and others 1992;Mencuccini and Grace 1994;Hebert and Jack 1998;Maherali and DeLucia 2001) and in species-poor tropical forests in Hawaii (Harrington and others 1995;Austin and Vitousek 1998;Ares and Fownes 1999). However, we are only aware of one study (Bussotti and others 2000) along a rainfall gradient focusing on the LAI of a temperate broad-leaved tree species.…”
Section: The Leaf Area-water Supply Relationship In Forestsmentioning
confidence: 95%
“…Stored water may contribute to transpiration in trees during diurnal cycles [60] and to the ability of plants to thrive in dry habitats [137]. However, field comparisons of ponderosa pine trees growing in contrasting habitats (desert vs. mountain) did not evidence any difference in water storage between habitats [93]. In pine dominated forests, the strategy in response to increasing atmospheric evaporative demand is to shift the relative allocation to leaves vs. sapwood and therefore to rise K L .…”
Section: Water Storage Capacity In the Sapwoodmentioning
confidence: 99%
“…Sensitivity analyses of varying k s with elevation (e.g. Maherali and DeLucia, 2001) did not result in significant differences in the model output, and so, for simplicity we held k s constant across sites. Comparison to the observations was facilitated by normalizing predictions relative to the highest observed values, constraining the upper limit of the predictions (Oren et al, 1999).…”
Section: Modellingmentioning
confidence: 99%